Determining artificial ageing methods and evaluating properties of universal composite resin: a review and proposed protocol / Nur Fatima Azzahara Mohamad Habibullah ... [et al.] - Mohamad Habibullah, Nur Fatima Azzahara; Ishak, Hayati; Mohammad, Norazlina; Anuar, Muhammad Alif Faiz; Amir, Amalina; Ismail, Ikmal Hisham (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Objective: Our aim is to propose a method for determining a more convenient artificial ageing (AA) protocol, which may be used to compare the optical / mechanical properties of universal to conventional composite. Methods: Artificial ageing (AA) protocol was adapted from (Alp et al., 2018) for thermocycling and (Jasin et al., 2018) for static immersion, which arbitrarily simulating 6 and 7 months of oral environment, respectively. In phase 1, Filtek Z350XT will be used to be immersed in coffee solution (test group) with distilled (control group) water. Colour changes will be measured and calculated using the CIEDE2000 formula and data will be statistically analysed to determine a meeting time point of colour change occurrence. Measurement will be repeated thrice to validate the new static emersion method. In phase 2, this new static immersion AA protocol will be used to compare Omnichroma's® colour stability with translucency to the Filtek Z350XT®. In phase 3, SEM EDS will be used to measure quantitative and qualitatively the occurrence of subsurface properties changes in Omnichroma® and Filtek Z350XT®. Finally, the discs’ microhardness will be evaluated. Significance: Presently, it is very difficult to precisely simulate the oral environment. In comparison to thermocycling, static immersion is a more convenient AA method. Establishing an evidence-based protocol may well potentially serve as a guide for researchers to assuredly select the more simplified AA protocol for future dental material development and clinical usage scenarios.